Characterization of pharmaceuticals, personal care products, and polybrominated diphenyl ethers in lake sturgeon serum and gametes. (November 2020) - Banda, Jo A.; Gefell, Dan; An, Viktoriya; Bellamy, Amber; Biesinger, Zy; Boase, James; Chiotti, Justin; Gorsky, Dimitry; Robinson, Timothy; Schlueter, Scott; Withers, Jonah; Hummel, Stephanie L.
Abstract: Recent research suggests contaminants of emerging concern (CECs) are widespread and environmentally relevant concentrations can impact fishes. However, little is known about impacts of CECs to long-lived or rare species. The objective of this study was to characterize CEC concentrations in lake sturgeon ( Acipenser fulvescens ) serum and gametes. Blood serum was collected non-lethally from lake sturgeon at four lower Great Lakes basin sites: Detroit, upper Niagara, lower Niagara, and St. Lawrence rivers; additionally, gametes were collected from lake sturgeon in the St. Lawrence River. Samples were analyzed for pharmaceuticals and personal care products (PPCPs) and polybrominated diphenyl ethers (PBDEs). Overall, 44 different PPCPs were identified in serum and gamete samples across sites, with 22 PPCPs identified in at least 25% of serum samples and three PPCPs identified in 25% of gamete samples. PPCP concentrations in serum and gametes ranged from 0.00208 to 130 ppb and 0.00538–190 ppb, respectively. NMDS ordination revealed differences in the presence and concentrations of PPCPs in lake sturgeon serum across sites, however, N, N-diethyl-meta-toluamide (DEET), hydrocortisone, benztropine, and amitriptyline were detected in at least one serum sample at all sites. Additionally, DEET, 10-hydroxy-amitriptyline, and sertraline were detected in ≥25% of gamete samples collected from the St. Lawrence River. Twenty-six PBDE congeners were identified in 25% of serum samples and 24 were identified in 25% of gamete samples. PBDEs in serum were present across all sites and in gametes of St. Lawrence River lake sturgeon, and total PBDE concentrations in serum and gametes ranged from 0.184 to 12.7 ppb and 0.0826–0.44 ppb, respectively. Managers of lake sturgeon populations may need to consider the impacts of CECs if reproductive, developmental, behavioral, growth effects, or mortality are observed in the Great Lakes basin or other areas that are impacted by increased exposures to PPCPs and PBDEs. Graphical abstract: Image 1 Highlights: PPCPs and PBDEs were identified in all lake sturgeon serum and gamete samples. 44 PPCPs were identified in serum and gamete samples across sites. At least 20 PBDEs were identified in every serum sample at every site. PBDE #47 had the highest mean and median concentrations in serum and milt. Management strategies should consider potential for risk via PPCP and PBDE exposure. Abstract : Main Finding: Contaminants of emerging concern are found in lake sturgeon serum and gametes which could be affecting their biology and ultimately populations.